Rumors management requirements in organizational relationships; From the perspective of the Holy Quran - Akram Goodarzi; Mona Afzali qadi (Religion & Communication, 2021)
The purpose of this study is to identify the needs of rumor management in organizational relationships from the perspective of the Holy Quran. Gossip is a fact of formal and informal communication. This phenomenon includes an unapproved proposition that is passed from one person to another, It often arises from people's suspicions, or is not based on solid evidence And it may be untrue, so it requires a favorable confrontation. The main question of the research is what are the requirements of rumor management in organizational relations from the perspective of the Holy Quran? The research method is inductive theme analysis during which the necessary data from the Holy Quran were collected and the basic, organizing and comprehensive themes were identified. The most important findings in the face of rumors are: preventing the publication of deviant news, ensuring certainty in fundamental actions, preventing possible harm, transparency of the position against deviations, awareness of the manifestations of deception, maintaining sanctities and links, dealing authoritatively with Threat factors and ...;The most important findings in creating rumors are: avoiding the violation of the rights of others, observing honesty of speech, protection from rumors. Based on the findings, the requirements are considered necessary due to the positions of a priori exposure, posterior exposure and creation. Some requirements are necessary in special circumstances and others are common to some situations. Also, in the face of rumors, knowing the truth or falsity of a rumor and in creating rumors, its true or unreal nature, is effective in determining the requirements.